If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2x(x + -1) = x + -2(x + -1) Reorder the terms: 3x + -2x(-1 + x) = x + -2(x + -1) 3x + (-1 * -2x + x * -2x) = x + -2(x + -1) 3x + (2x + -2x2) = x + -2(x + -1) Combine like terms: 3x + 2x = 5x 5x + -2x2 = x + -2(x + -1) Reorder the terms: 5x + -2x2 = x + -2(-1 + x) 5x + -2x2 = x + (-1 * -2 + x * -2) 5x + -2x2 = x + (2 + -2x) Reorder the terms: 5x + -2x2 = 2 + x + -2x Combine like terms: x + -2x = -1x 5x + -2x2 = 2 + -1x Solving 5x + -2x2 = 2 + -1x Solving for variable 'x'. Reorder the terms: -2 + 5x + x + -2x2 = 2 + -1x + -2 + x Combine like terms: 5x + x = 6x -2 + 6x + -2x2 = 2 + -1x + -2 + x Reorder the terms: -2 + 6x + -2x2 = 2 + -2 + -1x + x Combine like terms: 2 + -2 = 0 -2 + 6x + -2x2 = 0 + -1x + x -2 + 6x + -2x2 = -1x + x Combine like terms: -1x + x = 0 -2 + 6x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-1 + 3x + -1x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + 3x + -1x2)' equal to zero and attempt to solve: Simplifying -1 + 3x + -1x2 = 0 Solving -1 + 3x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 1 + -3x + x2 = 0 Move the constant term to the right: Add '-1' to each side of the equation. 1 + -3x + -1 + x2 = 0 + -1 Reorder the terms: 1 + -1 + -3x + x2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x + x2 = 0 + -1 -3x + x2 = 0 + -1 Combine like terms: 0 + -1 = -1 -3x + x2 = -1 The x term is -3x. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3x + 2.25 + x2 = -1 + 2.25 Reorder the terms: 2.25 + -3x + x2 = -1 + 2.25 Combine like terms: -1 + 2.25 = 1.25 2.25 + -3x + x2 = 1.25 Factor a perfect square on the left side: (x + -1.5)(x + -1.5) = 1.25 Calculate the square root of the right side: 1.118033989 Break this problem into two subproblems by setting (x + -1.5) equal to 1.118033989 and -1.118033989.Subproblem 1
x + -1.5 = 1.118033989 Simplifying x + -1.5 = 1.118033989 Reorder the terms: -1.5 + x = 1.118033989 Solving -1.5 + x = 1.118033989 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = 1.118033989 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = 1.118033989 + 1.5 x = 1.118033989 + 1.5 Combine like terms: 1.118033989 + 1.5 = 2.618033989 x = 2.618033989 Simplifying x = 2.618033989Subproblem 2
x + -1.5 = -1.118033989 Simplifying x + -1.5 = -1.118033989 Reorder the terms: -1.5 + x = -1.118033989 Solving -1.5 + x = -1.118033989 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = -1.118033989 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = -1.118033989 + 1.5 x = -1.118033989 + 1.5 Combine like terms: -1.118033989 + 1.5 = 0.381966011 x = 0.381966011 Simplifying x = 0.381966011Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.618033989, 0.381966011}Solution
x = {2.618033989, 0.381966011}
| 4x+5=6-3(x-2) | | h(t)=24t^2+96t+880 | | -2x+11x-17=0 | | (0.3/x)^-1 | | 36=7x+6 | | 99*exp(0.25*x)=100 | | 2+4x=-3x+9 | | sin(3x-15)=0.5 | | a/3+6=9 | | (x+2)(x-4)=5x-7 | | 10-6*2+9/3= | | 7x=-24+x | | 3x-5y-6=0 | | 5x^3+3x^2+2x+8=0 | | 7d-2=4(d-1) | | w^2+14wx+49x^2=0 | | 1/f=0.6(1/4+1/6) | | y=(2x+9)^1/4 | | 5x+60=75 | | (x+yi)+(3-3i)=18 | | 6x^2+12x=-9 | | 3x-(11-2x)=4 | | x/3+3/x=0 | | 2x+x-5=10 | | 2(x-5)+y=10 | | 16x-2(3)=74 | | 16(2+y)-2y=74 | | 3X+6Y=288 | | 288=(3x+6y) | | 1+y+2y=12 | | 288=3X+6Y | | 8x^3-x^4=0 |